Inapparent dengue in a community living among dengue-positive Aedes mosquitoes and in a hospital in Klang Valley, Malaysia - Tan, Wing; Liew, Jonathan Wee Kent; Selvarajoo, Sivaneswari; Lim, Xin Ying; Foo, Chuan Jie; Refai, Wardha F.; Robson, Noor Zurani; Othman, Sajaratulnisah; Abdul Hadi, Haireen; Mydin, Fadzilah Hanum Mohd; Malik, Tun Firzara Abdul; Lau, Yee Ling; et al. (Elsevier, 2020)
The public health burden of dengue is most likely under reported. Current dengue control measures only considered symptomatic dengue transmission. Hence, there is a paucity of information on the epidemiology of inapparent dengue. This study reports that many people have been unknowingly exposed to dengue infection. Almost 10% and 70% of individuals without any history of dengue infection and living in a dengue hotspot, in Selangor, Malaysia, were dengue IgM and IgG positive respectively. When dengue-positive mosquitoes were detected in the hotspot, 11 (6.3%) of the 174 individuals tested were found to have dengue viremia, of which 10 were asymptomatic. Besides, upon detection of a dengue-infected mosquito, transmission was already widespread. In a clinical setting, it appears that people living with dengue patients have been exposed to dengue, whether asymptomatic or symptomatic. They can either have circulating viral RNA and/or presence of NS1 antigen. It is also possible that they are dengue seropositive. Collectively, the results indicate that actions taken to control dengue transmission after the first report of dengue cases may be already too late. The current study also revealed challenges in diagnosing clinically inapparent dengue in hyperendemic settings. There is no one best method for diagnosing inapparent dengue. This study demonstrates empirical evidence of inapparent dengue in different settings. Early dengue surveillance in the mosquito population and active serological/virological surveillance in humans can go hand in hand. More studies are required to investigate the epidemiology, seroprevalence, diagnostics, and control of inapparent dengue. It is also crucial to educate the public, health staff and medical professionals on asymptomatic dengue and to propagate awareness, which is important for controlling transmission. © 2020 Elsevier B.V.